A new species of Scolelepis (Polychaeta: Spionidae) from sandy beaches in China, with a review of Chinese Scolelepis species - Zhou, Jin; Ji, Weiwei; Li, Xinzheng (Zootaxa, 2009)
A new species of Spionidae, Scolelepis (Scolelepis) daphoinos sp. nov., is described and illustrated from northern China seas. The species was frequently encountered and highly abundant on sand beaches, but rarely found in subtidal areas. It was formerly misidentified as S. (S.) squamata (Müller, 1806) in China but differed from the latter species in several details in morphology, including the presence of obvious reddish pigmentation patches and the absence of unidentate hooded hooks. Another two Scolelepis species, S. (S.) lingulata Imajima, 1992 and S. (S.) variegata Imajima, 1992, are reported for the first time from Chinese waters. Two species of Scolelepis, S. (S.) globosa Wu & Chen, 1964 and S. (S.) lefebvrei (Gravier, 1905), were reported previously; therefore, five species in this genus are known from China in total. A key to all Scolelepis species from Chinese waters is provided.